International collaborative ventures in U.S. manufacturing (Ballinger Pub. Co., 1988)
This paper surveys recent trends and implications in collaboration between U.S. and foreign manufacturing firms, drawing on a comparative study of these activities in eight manufacturing industries. The causes of recent growth in international collaboration are both technological and policy-related. The structure of collaboration, the activities incorporated into collaborative ventures, and the amount and direction of technology transfer between U.S. and foreign firms all vary across industries.